The contribution of weather forecast information to agriculture, water, and energy sectors in East and West Africa: A systematic review - Agyekum, Thomas Peprah; Antwi-Agyei, Philip; Dougill, Andrew J. (Frontiers in Environmental Science, 2022)
The provision of timely and precise weather information could reduce the vulnerability of people to climate change risks. In this study, we conducted a systematic review to synthesise the existing evidence on weather information service for the agriculture, water and energy sectors of East and West Africa and identified priorities for future research. The review identified relevant peer-reviewed publications using ScienceDirect and Scopus databases for original research articles published in English from 2000 to 2022. After applying eligibility criteria, the most pertinent 25 articles were included in the final review. The review revealed that weather information studies had focused more on the agriculture sector than energy production and water resource management. Users of weather information mainly accessed information related to rainfall and temperature, and the information was accessed mainly through radio, mobile phones and television. Most of the information provided focused on generic meteorological forecasts instead of a tailored impact-based forecast. Few users could access or benefit from the information produced due to poor communication and technical understanding of weather information. In addition, lack of downscaled information, logistics and trust hindered the uptake and use of climate information. Consequently, mainstreaming capacity building of key stakeholders will promote effective adoption and strengthening of climate information service across space, especially in West and East Africa.